Why is there no Socialism in Europe? The Technocratic Neoliberal turn in European Economics - Colatrella, Steven (Journal of Management Policy and Practice, 2019)
The neoliberal turn in European economics was not largely the work of economists, but of technocrats in finance ministries and central banks. Governments accepted their lead, responding to the loss of relative power to electorates and to organized labor. Politicians sought solutions to problems of economic management arising from the end of the Bretton Woods system of fixed exchange rates and from the Oil Crises of the 1970s. But in siding with technocrats informed by monetarist and neoliberal economists’ arguments, and in ceding to central bankers especially control of economic policy and EU negotiations over the Euro, politicians opened the door to increased power in the hands of mobile capital allied with technocrats in Finance Ministries and Central Banks. The most that can be said of economists as a profession is that they went along for the ride, happy with a new situation that celebrated their importance as consliglieri to the powerful.